(untitled) (Comunicação & Inovação, 2016)
Our aim is to understand the city from its artistic expressions that take place in the port area of Rio de Janeiro, which is historically marked by intercultural and polyphonic encounters. Therefore, we pay attention to the possible dialogues between thelocal culture, which has Pedra do Sal samba as itsmost symbolic expressions, and the political interventions promoted by the city administrators. We ask: What is really at stake in the revitalization discourse of the port area in Rio de Janeiro? Which aspects of the contemporary society can be pointed out in this communicative and urban project?